Sekcija "Arheologu un etnogrāfu pētījumi Latvijā 2018. – 2020. gadā" : Tēžu krājums - Latvijas Universitāte. 79. starptautiskā zinātniskā konference (Latvijas Universitātes Latvijas vēstures institūts, 2021)
Krājumā apkopotas 2021. gada 11. martā Latvijas Universitātes 79. starptautiskās zinātniskās konferences ietvaros Latvijas Universitātes Latvijas vēstures institūta organizētās sekcijas “Arheologu un etnogrāfu pētījumi Latvijā 2018. – 2020. gadā” nolasīto referātu tēzes. Tēzēs atspoguļojas LU Latvijas vēstures institūta, LU Vēstures un filozofijas fakultātes un Latvijas Nacionālā vēstures muzeja arheologu ieguldījums arheoloģiskā mantojuma un senvēstures aktuālu jautājumu izpētē. Tēzēs ietvertās atziņas balstītas padziļinātos, starpdisciplināros pētījumos, tās atspoguļo jaunu tēmu un arheoloģiskā materiāla interpretāciju meklējumus, kā arī arheoloģisko pieminekļu apzināšanas un izrakumu metodiskos aspektus. Etnogrāfu referātu tēzes prezentē pēdējos gados Latgalē organizēto etnogrāfisko ekspedīciju veikumu. Tas ietver materiālā un nemateriālā kultūras mantojuma, kas saistīts ar tekstīliju (tostarp arī katoļu baznīcu liturģisko tekstīliju), apģērba, rokdarbu vēstures izpēti. Etnogrāfu pētīto tēmu lokā novitāte ir etnogrāfisko un frīku šovi Latvijā 19. un 20.gs. mijā. This volume brings together the abstracts of papers presented at the session “Archaeological and ethnographic research in Latvia, 2018–2020” held by the Institute of Latvian History, University of Latvia on 11 March 2021 in the frame of the 79th International Scientific Conference of the University of Latvia. The abstracts reflect the contribution by archaeologists from the Institute of Latvian History, University of Latvia, Faculty of History and Philosophy, University of Latvia and the National History Museum of Latvia to the study of the archaeological heritage and topical issues in prehistory. The ideas advanced in the abstracts are based on in-depth interdisciplinary research and reflect an orientation towards novel themes and interpretations of archaeological material, as well as methodological aspects of archaeological survey and excavation. The abstracts of the papers by ethnographers present the results of ethnographic fieldwork undertaken in recent years in the Latgale region. This encompasses the study of tangible and intangible heritage relating to the history of textiles (including liturgical textiles from Catholic churches), dress and handicrafts. Ethnographic and freak shows in Latvia at the turn of the 20th century constitute a novel topic in ethnographic research.
79th International Scientific Conference of the University of Latvia. Session “Archaeological and ethnographic research in Latvia, 2018–2020". Abstracts.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Ethnology; Research Subject Categories::NATURAL SCIENCES::Earth sciences; Latvijas arheoloģija un etnogrāfija; pieminekļu apzināšana; arheoloģiskie izrakumi; starpdisciplināri pētījumi; tekstīlijas